Review of Standard and Advanced Surgical Treatments for Invasive Bladder Cancer (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to the Global Cancer Observatory, in recent decades, about 400 thousand primary patients diagnosed with bladder cancer have been identified, and in 2020 the number of patients registered with bladder cancer has already reached 573.3 thousand (3% of all cancer cases). Men are much more likely to suffer from this cancer pathology and the ratio is approximately 1:9. In the overall structure of cancer incidence in 2020, breast cancer took 17th place in women and 6th place in men. This pathology caused death in 212.5 thousand patients in 2020, and the mortality rate per 100 thousand men was 3.3 cases and 0.9 cases in women. Invasive bladder cancer is a cancer that is becoming increasingly common among men. Radical cystectomy is widely used as the primary treatment for this type of tumor. In order to improve the quality of life of patients, which is no less important than the survival rate, specialists in modern practical oncology have introduced more than 46 types of urine diversion into practice in the period after such highly traumatic operations. Complications after these operations and the problem of their elimination also remain relevant.